2022
DOI: 10.3390/vetsci9060291
|View full text |Cite
|
Sign up to set email alerts
|

Feline Gastrointestinal Eosinophilic Sclerosing Fibroplasia—Extracellular Matrix Proteins and TGF-β1 Immunoexpression

Abstract: Feline gastrointestinal eosinophilic sclerosing fibroplasia (FGESF) has been described as an inflammatory disorder with an eosinophilic component with etiopathogenesis that is still unknown. Sixteen intestinal samples from two veterinary diagnostic services (2014–2017) were included in the study. A histopathological criterion classified the cases into three grades (mild, moderate, and severe) according to the distribution of the lesions and the course. An immunohistochemical study of collagen I, collagen III, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…Possible reasons for this observation are that cats that enter clinical remission have less or no IF or that, in the event of CIE relapse, the presence of IF results in difficulty in re‐gaining clinical remission. A recent study identified collagen I in later‐stage intestinal fibrosis relative to collagen III 12 . Therefore, diagnostic delay in identifying IF could further correlate advanced collagen deposition with failure to attain clinical remission.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Possible reasons for this observation are that cats that enter clinical remission have less or no IF or that, in the event of CIE relapse, the presence of IF results in difficulty in re‐gaining clinical remission. A recent study identified collagen I in later‐stage intestinal fibrosis relative to collagen III 12 . Therefore, diagnostic delay in identifying IF could further correlate advanced collagen deposition with failure to attain clinical remission.…”
Section: Discussionmentioning
confidence: 99%
“…In humans with IBD, IF is an expected complication and a distinct cause of patient morbidity and mortality 5,7‐9 . In humans with IBD, myofibroblasts have been identified as key cellular mediators of collagen deposition, with collagen types I and III considered the 2 major ECM proteins associated with IF 10‐12 . Intestinal fibrosis persists in a self‐perpetuating manner in the absence of inflammation 13 with evidence also indicating that ECM stiffness itself is capable of perpetuating collagen deposition 14 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 The exuberant collagen deposition and fibrosis are likely mediated by the eosinophils and are suspected to involve dysregulation of expression of extracellular matrix protein and transforming growth factor-β 1 . 16 The reported prognosis in FESF is highly variable, and likely depends on the clinical presentation. Cases presenting with locally aggressive unresectable masses have a poor reported outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Gastrointestinal eosinophilic sclerosing fibroplasia in cats is likely underdiagnosed because these mass lesions can be misinterpreted as lymphoma, granuloma, fibrosarcoma, adenocarcinoma, and mast cell tumor, and the histopathological diagnosis can be challenging 2,6‐8 . Immunohistochemical staining for transforming growth factor β1 can aid diagnosis 9 . This disease is most commonly seen in middle aged and male cats of all breeds, with Ragdolls being overrepresented and the disease is also reported in Maine Coons, Persians, Exotic Shorthairs, Bengal, and Scottish fold cats 1,2,10‐12 .…”
Section: Introductionmentioning
confidence: 99%